ELASTISITAS PENYERAPAN TENAGA KERJA PADA SEKTOR –SEKTOR PEREKONOMIAN DI KABUPATEN MUARO JAMBI - Azizah Azizah (Universitas Batanghari Jambi, 2014)
Regional economic development has the main purpose of that is to increase and expand job opportunities for the people of the area. To achieve this purpose, the local government and the community should jointly take the initiative leveraging the existing potential optimally in developing the region's economy for the benefit of society. Now that the problem in this study is how the elasticity and the coefficient of energy-sector jobs in economic sectors featured in Jambi Regency Floating Market. Whereas in this study is to analyze the coefficient of elasticity and energy-sector jobs in economic sectors featured in Jambi Regency Floating Market. Over the period 2008-2012 from the elasticity of labor absorption in each sector shows the condition of one year ie in 2010 occurred inelastic or elastic increase in PDRB of labor absorption. This scenario is possible because in 2010 there was a global economic shocks that also have an impact on the acceptance of each sector to the absorption of labor in Jambi Regency Muaro also down. But .At trade, hotels and restaurants in Muaro Jambi Regency during the period 2008-2012 shows all criteria elastic means trade, hotels and restaurants are able to contribute in absorbing labor and quite resistant to shock the global economic crisis. From the estimated coefficients of the variables known that labor absorption in all sectors showed positive figures and large enough to contribute to the growth of the Gross Regional Domestic Product (PDRB) in Jambi Regency Muaro.Keyword: PDRB, Elasticity